Analisis Pengaruh Likuiditas, Leverage dan Ukuran Perusahaan terhadap Agresivitas Pajak - Larasati, Larasati; Djunaedi, Mira Kartika Dewi (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2024)
Taxes is one of sources income for countries, in which taxes contribute 71% of total revenue. Taxes are considered as a burden by the company, it is necessary to do a strategy to reduce the tax burden. Reducing the tax will cause companies to be aggressive towards taxes. The purpose of this study is to determine the effect of liquidity, leverage and company size on tax aggressiveness in consumer goods subsector manufacturing companies listed on the Indonesia Stock Exchange during the period 2017-2021. The type of data used in this study is secondary data from financial statements and company annual reports sourced from the official website of the Indonesia Stock Exchange (IDX). Determination of the sample using purposive sampling method and obtained a sample of 120 based on certain criteria. The analytical method used is multiple linear regression using the Stata 17 program. The results of this study indicate that liquidity and firm size have no significant effect with a negative direction on tax aggressiveness. While, leverage leads to a positive direction and has no significant effect on tax aggressiveness.